48.0k views
1 vote
If f(x) =5x^3-2 and g(x)= x+1, find (f-g)(x)

If f(x) =5x^3-2 and g(x)= x+1, find (f-g)(x)-example-1

2 Answers

1 vote
That would be 5x^3 - 2 - (x + 1) = 5x^3 - 2 - x - 1

Answer is 5x^3 - x - 3.

Its B
User Lupa
by
5.9k points
5 votes

Answer:

Option B is correct


(f-g)(x) = 5x^3-x-3

Explanation:

Given the functions:


f(x) =5x^3-2

g(x)= x+1

We have to find (f-g)(x).


(f-g)(x) = f(x)-g(x)

Substitute the given values we have;


(f-g)(x) = 5x^3-2-(x+1)


(f-g)(x) = 5x^3-2-x-1

Combine like terms;


(f-g)(x) = 5x^3-x-3

Therefore, the value of
(f-g)(x) is,
5x^3-x-3

User Gongshw
by
6.3k points